A novel outer-membrane-associated protease in Escherichia coli. - Sugimura, K (1988)
Human gamma interferon produced by recombinant Escherichia coli was degraded by endogenous protease after cell disruption. Specific cleavages took place at the center of two pairs of basic amino acids (Lys-131-Arg-132 and Arg-142-Arg-143) in the C-terminal region, giving rise to products with molecular weights of 17,500 and 16,000. The proteolytic activity was associated with the outer membrane of E. coli. It was insensitive to the protease inhibitors diisopropylfluorophosphate, phenylmethylsulfonyl fluoride, tosyl-L-lysine chloro-methyl ketone, EDTA, and p-chloromercuribenzoate. Benzamidine and the bivalent cations Zn2+ and Cu2+ inhibited the activity. Dynorphin A(1-13) (Tyr-Gly-Gly-Phe-Leu-Arg-Arg-Ile-Arg-Pro-Lys-Leu-Lys) was a good substrate and was preferentially cleaved at the center of Arg-6-Arg-7. Neither the amino nor carboxyl sides of Arg-9 and Lys-11 were digested. These results indicate that the protease specifically cleaves the peptide bond between consecutive basic residues and therefore is different from the known membrane enzymes, proteases IV, V, and VI. We have designated this new enzyme protease VII.